The infrastructural lands of urban sprawl: planning potentials and political perils. Issue 2 (March 2017) - Silva, Cristian Alejandro
Abstract : Urban sprawl in Latin America has been seen as a factor in social segregation, poverty concentration, lack of services and transport, environmental detriment, and constraints on the public budget. However, in this scenario, some undeveloped areas are seen as opportunities – particularly infrastructural land – for urban mega-projects. Although these initiatives are based on cutting-edge narratives of urban sustainability, expectations of project-based rationalities clash with the absence of political frameworks and unanticipated constraints that illustrate a wide set of political perils. Using a former airport now included within the suburban sprawl of Santiago de Chile as an example, this paper provides evidence of a sequence of political drawbacks in its reconversion, and the fragility of planning frameworks in their capacity to mediate between urban development pressures and resistance to them. What is also clear is the fact that recovering in-between landscapes of sprawl still rests on 'projects' instead of planning policies.